RACING HEART UNDER STORMY SKIES: A JOURNEY THROUGH AGRANULOCYTOSIS TO THYROID STORM - Tan, Jia Miao; Wong, Mark Vin; Bernard, Dorothy Maria Anthony; Foo, Siew Hui (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Thyroid storm is a rare but life-threatening exacerbation of thyrotoxicosis characterised by multi-system dysfunction. Its shared features with sepsis may pose a significant diagnostic challenge. We describe a patient with Graves’ disease who developed carbimazole-induced agranulocytosis followed by thyroid storm necessitating therapeutic plasma exchange (TPE) and urgent thyroidectomy. CASE A 31-year-old female with newly diagnosed Graves’ disease on carbimazole 40 mg daily presented with palpitations and right hypochondriac pain. Initial investigation showed elevated FT4 at 31 pmol/L (7.86-14.41 pmol/L), suppressed TSH at 0.03 uIU/mL (0.38-5.33 uIU/mL) with cholestatic transaminitis. On day 3 of admission, she developed agranulocytosis with an absolute neutrophil count (ANC) of 0.06 x 10⁹/L, hence carbimazole was withheld. Granulocyte-colony stimulating factor was initiated along with a broad-spectrum antibiotic to cover for neutropenic sepsis. The ANC normalised after three days, but she developed spiking fever up to 40.8°C, associated with persistent vomiting followed by hypotension and tachycardia. Biochemical tests revealed rising FT4 to 44.5 pmol/L and hyperbilirubinemia. Initiation of glucocorticoids upon withholding carbimazole was delayed due to concern of sepsis. Diagnosis of thyroid storm was made and urgent TPE was initiated along with high-dose intravenous glucocorticoids and esmolol infusion. She showed immediate clinical improvement with defervescence and stabilization of hemodynamic parameters after the first cycle of TPE. Total thyroidectomy was performed after two cycles of TPE, and she was discharged well on day 30. CONCLUSION This case highlights the challenge of distinguishing thyroid storm from sepsis in the setting of carbimazole-induced agranulocytosis. It underscores the importance of prompt recognition and timely intervention of thyroid storms to prevent morbidity and mortality. Early initiation of TPE as bridging therapy before definitive therapy in the setting where antithyroid drug was contraindicated provided rapid control of thyrotoxicosis and was well tolerated.